Reducing parenting stress among Muslim mothers during the COVID-19 pandemic through spiritual mindfulness training - Hertinjung, Wisnu Sri; Laksmadita, Citra Tyas; Ruhaena, Lisnawati; Sulandari, Santi; Kusumawati, Dwi Arsinta (Humanitas: Indonesian Psychological Journal, 2023)
An imbalance between nurturing expectations and available resources during the COVID-19 pandemic increases the risk of parental stress. This study aimed to reduce parental stress through spiritual mindfulness training among Indonesian Muslim mothers. This study applied the embedded experimental model, one part of the mixed method design, where qualitative data is used to clarify the results of the experimental data. The experimental design used was the pretest-posttest control group design.  Twenty individuals were randomly assigned to experimental and control groups. The Parental Stress Scale was used to assess parental stress. The Wilcoxon and Mann-Whitney U tests were used to compare parental stress levels before and after spiritual mindfulness training. The hypothesis test results show that spiritual mindfulness training effectively reduces parenting stress for Indonesian Muslim mothers. Observation data during the training process and analysis of the assignment sheet found that the two individuals actively participating in the training process and frequently filling out the assignment sheets reduced parental stress levels more than their more passive counterparts. Spiritual mindfulness training successfully decreases the parental stress of Muslim mothers, and it is strongly suggested that mothers practice training regularly to considerably control their stress.